Back Cover: MALDI Imaging‐Guided Microproteomic Analyses of Heterogeneous Breast Tumors—A Pilot Study. Issue 1 (17th January 2018) - Alberts, Deborah; Pottier, Charles; Smargiasso, Nicolas; Baiwir, Dominique; Mazzucchelli, Gabriel; Delvenne, Philippe; Kriegsmann, Mark; Kazdal, Daniel; Warth, Arne; De Pauw, Edwin; Longuespée, Rémi
Abstract : Matrix‐assisted laser desorption ionisation (MALDI)‐imaging coupled to laser microdissection (LMD)‐based microproteomics to study intratumor heterogeneity. MALDI imaging dataset from breast cancer FFPE tissue sections were segmented to draw intratumor proteomic heterogeneity. Tissue regions containing 3500 cells from different molecular clusters were collected by LMD and processed for further microproteomic analyses. The combination of MALDI imaging with LMD‐based microproteomics will pave the way to in‐depth characterization of intratumor heterogeneity in pathology. This is reported by Deborah Alberts, Charles Pottier, Nicolas Smargiasso, Dominique Baiwir, Gabriel Mazzucchelli, Philippe Delvenne, Mark Kriegsmann, Daniel Kazdal, Arne Warth, Edwin De Pauw and Rémi Longuespée, article number 1700062.